Strengthening Community Disaster Resilience Through The Integration of KKN Kebencanaan and PKM-MNM in Padang City - Daimon Syukri; Jonrinaldi Jonrinaldi; Susiana Susiana (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2026)
Disaster-prone regions require integrated and participatory approaches to enhance community resilience. This study presents a disaster-themed outreach program conducted by Universitas Andalas, integrating KKN Kebencanaan and the Program Kemitraan Masyarakat Membantu Nagari Membangun (PKM-MNM) Batch II, focusing on emergency disaster response in Kota Padang. The program was implemented across 16 locations using participatory methods, including hazard identification, mapping, clean water provision, disaster data collection, and community education. The results show improved access to clean water, enhanced disaster-related data availability, and increased community awareness of preparedness. The program also strengthened collaboration among stakeholders. This initiative highlights the strategic role of higher education institutions in building disaster-resilient communities.